THE EFFECT OF THYROXINE HORMONE AND RECOMBINANT GROWTH HORMONE (RGH) SOAKING ON THE RATE OF EGG YOLK ABSORPTION AND GROWTH OF TAWES FISH (Barbonymus gonionotus) - Yuniarti, Tristiana; Hastuti, Sri; Nugroho, Ristiawan Agung; Basuki, Fajar; Chilmawati, Diana; Saputra, Raka Gilang (Agency for Marine and Fisheries Extension and Human Resources, 2025)
Tawes fish (Barbonymus gonionotus), also known as lampan, is an indigenous freshwater species with significant economic value and cultivation potential. However, suboptimal growth remains a common challenge in aquaculture. Hormonal treatments such as thyroxine and rGH are known to enhance metabolic processes, potentially improving egg yolk absorption and larval growth. This study aimed to evaluate the effects of thyroxine and rGH hormone immersion on the rate of egg yolk absorption and development of newly hatched tawes fish larvae. The experimental design employed a CRD with four treatments and three replications: A (thyroxine 0 mg/L + rGH 2.5 mg/L), B (thyroxine 0.1 mg/L + rGH 0 mg/L), C (thyroxine 0 mg/L + rGH 2.5 mg/L), and D (thyroxine 0.1 mg/L + rGH 2.5 mg/L), with hormone immersion conducted for 60 minutes. The results demonstrated that the combined immersion of thyroxine and rGH significantly (P <0.05) improved the absolute weight gain, absolute length increment, and survival rate of tawes fish larvae. The highest values for absolute weight (0.043±0.002 g) and length (12.77±0.15 mm) were observed in treatment D (thyroxine 0.1 mg/L + rGH 2.5 mg/L), while the best survival rate (70.00±2.00%) was recorded in treatment A (thyroxine 0 mg/L + rGH 2.5 mg/L). These findings suggest that the combined use of thyroxine and rGH can effectively enhance the early growth and development of tawes fish larvae.